Communication Patterns During Application New Normal Covid-19 Protocol (Qualitative Descriptive Study In Seluma Regency) - Yogi Arman Sugiarto; Sapta Sari; Vethy Octaviani (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study was to determine the pattern of communication in the mass of the application of the Covid-19 New Normal protocol in the V hamlet of Sidoluhur village, Seluma district. This research method is fleld research with a qualitative approach. The data was collected by means of observation, interview and documentation techniques. The theory used in this study is the Effendy Communication Pattern, which states that there are three patterns of communication, namely one-way, two-way, and multi-direction. The resource persons of this research were the Sidoluhur Village Government and the Dusun V. Community. The results showed that the Communication Pattern between the Sidoluhur Village Government and the Dusun V Community was a One-way Communication Pattern because in carrying out prevention socialization there was no direct interaction and mass gathering. This can be seen from the socialization activities carried out but it has not received a good response from the people of Dusun V Sidoluhur Village. The factors that cause a lack of public awareness about the importance of good communication patterns during the Covid-19 New Normal are internal factors in the community itself.